2006
DOI: 10.1109/tie.2006.882012
|View full text |Cite
|
Sign up to set email alerts
|

DC-Bus Signaling: A Distributed Control Strategy for a Hybrid Renewable Nanogrid

Abstract: Abstract-A dc nanogrid is a hybrid renewable system since renewable sources supply the average load demand, while storage and nonrenewable generation maintain the power balance in the presence of the stochastic renewable sources. The system is power electronic based, with converters being used to interface both the sources and loads to the system. The nanogrid is controlled using dc-bus signaling (DBS), a distributed control strategy in which the control nodes, the source/storage interface converters, induce v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(82 citation statements)
references
References 8 publications
0
68
0
4
Order By: Relevance
“…Apart from that, decentralized methods, such as bus signaling [40], can realize control and coordination functions without involving either a central controller or DCLs. Taking bus signaling as an example, it uses the dc bus itself as the communication link to exchange essential information.…”
Section: Distributed and Decentralized Applicationsmentioning
confidence: 99%
“…Apart from that, decentralized methods, such as bus signaling [40], can realize control and coordination functions without involving either a central controller or DCLs. Taking bus signaling as an example, it uses the dc bus itself as the communication link to exchange essential information.…”
Section: Distributed and Decentralized Applicationsmentioning
confidence: 99%
“…Authors also demonstrated that decentralized control can overcome the drawback of centralized and distributed techniques, maintaining optimal operation while keeping the stability and reliability of the system. In addition, many works have emphasized that DC-bus signaling (DBS) is the most favorable method for coordinating the performance of multiple DC converters in DC microgrids [9,18,19]. According to the DBS concept, the scheduling of sources is achieved by making the operation of converters correspond with the level of bus voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The details of DBS implementation originally proposed by [21] is given in [15] and [16]. The two main objectives of converters in DC MG operation are to regulate the system voltage deviation and power flow, which may create control conflict since only one operating mode is possible at a time.…”
Section: Introductionmentioning
confidence: 99%